Dad is fat [compact disc, unabridged] - Gaffigan, Jim (Random House Audio, 2013)
Reminiscent of Bill Cosby's 'Fatherhood,' 'Dad is Fat ' is sharply observed, explosively funny, and a cry for help from a man who has realized he and his wife are outnumbered in their own home.